2020
DOI: 10.2196/21604
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of COVID-19 Severity Using Chest Computed Tomography and Laboratory Measurements: Evaluation Using a Machine Learning Approach

Abstract: Background Most of the mortality resulting from COVID-19 has been associated with severe disease. Effective treatment of severe cases remains a challenge due to the lack of early detection of the infection. Objective This study aimed to develop an effective prediction model for COVID-19 severity by combining radiological outcome with clinical biochemical indexes. Methods A total of 46 patients with COVID-19 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…They segmented CT imaging through a deep CNN to extract essential features and selected 12 laboratory tests that showed the largest change in the two groups of patients, mainly D-dimer, LDH and lymphocytes as predictors of higher mortality risk. Moreover, lymphocytes, neutrophils, D-dimer and platelets-large cell ratio demonstrated a significant correlation with selected CT features [101].…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest Ctmentioning
confidence: 89%
“…They segmented CT imaging through a deep CNN to extract essential features and selected 12 laboratory tests that showed the largest change in the two groups of patients, mainly D-dimer, LDH and lymphocytes as predictors of higher mortality risk. Moreover, lymphocytes, neutrophils, D-dimer and platelets-large cell ratio demonstrated a significant correlation with selected CT features [101].…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest Ctmentioning
confidence: 89%
“…Based on the number of enrolled images, 32,857 images (19,623‬ COVID-19 images and 13,234 Healthy images) classified by analysis were included. The AI algorithm based on the neural network was established in a number of research articles [ 21 , 22 , 23 , 25 , 26 , 27 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 41 , 42 , 43 , 47 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 57 ]. Among the included studies, twenty-nine models were selected for meta-analysis on DL assisted detection for predict COVID-19 [ 21 , 22 , 25 , 26 , 27 , 30 , 33 , 34 , 35 , 36 , 37 , 40 , 41 , 42 , 46 , 47 , 50 , 51 , 52 , 53 , 54 , 56 , 57 ] and fourteen models on ML assisted detection for predict COVID-19 [ 21 , 24 , 28 , 31 , 38 , 43 , 45 , 46 , 48 , 49 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Daowei Li et al, 2020, showed that the AUR score of ML was 0.93 [ 34 ]. However, in our study, pooled AUC in ML was higher, 0.97 (95% CI, 0.96-0.99).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been a proliferation of studies proposing prediction models based on various clinical parameters aimed at early stratification of deteriorating patients (Abdulaal et al, 2020;Aktar et al, 2021;Gao et al, 2020;Yan et al, 2020). These approaches are primarily based on traditional machine learning approaches (Aktar et al, 2021) such as support vector machines (SVM) (Gao et al, 2020), random forests (RF) (An et al, 2020), or deep neural networks based (DNN) (Li et al, 2020) methods specifically when it comes to analyzing X-ray or computed tomography (CT) images (Lassau et al, 2021). Despite these advances, we have yet to see a practical system, which could be used universally with an evidence of generalizability to help with early identification of patients, who develop severe clinical trajectory.…”
Section: Introductionmentioning
confidence: 99%